2012
DOI: 10.1002/brb3.36
|View full text |Cite
|
Sign up to set email alerts
|

Open‐field arena boundary is a primary object of exploration for Drosophila

Abstract: Drosophila adults, when placed into a novel open-field arena, initially exhibit an elevated level of activity followed by a reduced stable level of spontaneous activity and spend a majority of time near the arena edge, executing motions along the walls. In order to determine the environmental features that are responsible for the initial high activity and wall-following behavior exhibited during exploration, we examined wild-type and visually impaired mutants in arenas with different vertical surfaces. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 34 publications
4
72
2
1
Order By: Relevance
“…There was a decrease in the distance traveled by the BPA-exposed flies, although there was no significant change in the walking speed (velocity) that may alter the distance that they traveled during the course of the assay. Previous evaluations of exploratory behavior in Drosophila demonstrated higher initial spontaneous activity levels that decreased over time [83,90,91], but these higher levels were not observed in our experiment, as we had chosen a smaller duration (5 min) for the assay. Indeed, to ensure that the results were not confounded by other external factors such as fatigue and starvation, we chose a smaller arena (8 mm) and duration (5 min) for the assay.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…There was a decrease in the distance traveled by the BPA-exposed flies, although there was no significant change in the walking speed (velocity) that may alter the distance that they traveled during the course of the assay. Previous evaluations of exploratory behavior in Drosophila demonstrated higher initial spontaneous activity levels that decreased over time [83,90,91], but these higher levels were not observed in our experiment, as we had chosen a smaller duration (5 min) for the assay. Indeed, to ensure that the results were not confounded by other external factors such as fatigue and starvation, we chose a smaller arena (8 mm) and duration (5 min) for the assay.…”
Section: Discussioncontrasting
confidence: 71%
“…In circular arenas, Drosophila moves with small turn angles [91]. We observed a trend toward an increase in turn angle and a significant increase in the angular velocity of movement in the flies with an increase in the BPA concentration.…”
Section: Discussionmentioning
confidence: 81%
“…These authors suggest instead that A represents a behavioral artifact as a result of flies avoiding the midday sun by sheltering in the shaded part of the glass activity tube where the TriKinetics infrared detectors are located, leading to inappropriate triggering of the sensor and high activity counts. In apparent support of this model, they observed that flies in open-field Petri dish arenas did not show an A component under summer conditions, although this interpretation has been criticized (9), in part because Petri dishes are well known to be problematic for Drosophila open-field behavioral recordings (10). (4) studies, the classic per mutants were congenic with each other but were compared with three different wild-type strains so genetic background was not controlled.…”
Section: Significancementioning
confidence: 99%
“…Thigmotaxis proposes an animal's affinity for the boundary is due to arousal gained by contact with walls [26], [27]. However Drosophila do not prefer all walls equally, favoring boundaries over internal walls [29], arguing against a simple thigmotactic motivation. It has been further suggested that prevalence of straight trajectories with a failure to make frequent sharp turns would promote a high occupancy at the boundaries of arenas [30], but persistent straight trajectories was by itself is insufficient to account for the movement and positional preferences of Drosophila in an hourglass-shaped arena [29].…”
Section: Introductionmentioning
confidence: 99%